Coping behavior in diadic relations for partners with normative and disturbed development - Natalya S. Shipova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The study of the category of persons with impaired health is currently not sufficiently complete from a scientific point of view, but very significant from a social point of view. The article presents the results of a theoretical and empirical study of the coping behavior of individual and group subjects, namely dyads of partners of different health status: couples, including a partner with normative and impaired development; couples including both partners with developmental disabilities; couples consisting of normatively developing partners. The purpose of the study is a comprehensive analysis of the system of coping efforts in the dyad of partners in close relationships. The presence of a disease in one or both partners in a dyad is understood by us as stress, moreover, chronic, since we consider the status of disability in adults. At the same time, stress has the characteristics of both external and internal. Following foreign scientists, we believe that the disease represents general stress and is accompanied by specific functions, since the focus is on the physical illness of one partner, which adds dynamics to dyadic stress and the process of overcoming. We made an attempt to systematize the situation of the joint efforts of partners in tandem with impaired health. An analysis was made of the severity of individual and dyadic coping strategies in pairs of different groups, and a picture was analyzed of the correlation of the studied parameters with aspects of the quality of life, adaptation and cohesion of dyads, as well as the presence of health problems. A regression analysis of the impact of disability status on the complex of indicators studied was carried out. Thus, the specificity of coping behavior in dyads with different health status of partners is highlighted.